2006
DOI: 10.1093/ndt/gfl144
|View full text |Cite
|
Sign up to set email alerts
|

Hydrochlorothiazide in CLDN16 mutation

Abstract: Background. Hydrochlorothiazide (HCT) is applied in the therapy of familial hypomagnesaemia with hypercalciuria and nephrocalcinosis (FHHNC) caused by claudin-16 (CLDN16) mutation. However, the shortterm efficacy of HCT to reduce hypercalciuria in FHHNC has not yet been demonstrated in a clinical trial. Methods. Four male and four female patients with FHHNC and CLDN16 mutation, under long-standing HCT therapy (0.4-1.2 mg/kg, median 0.9 mg/kg, dose according to calciuria), aged 0.7-22.4 years, were included in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Unfortunately, thiazides neither yield a meaningful reduction in urinary calcium excretion nor delay the progression of CKD [76, 78, 93]. Moreover, thiazides can aggravate renal magnesium wasting, often leading to their discontinuation [5, 92, 94]. The serum magnesium level tends to remain low despite high-dose magnesium supplementation [78].…”
Section: Familial Hypomagnesemia With Hypercalciuria and Nephrocalcinmentioning
confidence: 99%
“…Unfortunately, thiazides neither yield a meaningful reduction in urinary calcium excretion nor delay the progression of CKD [76, 78, 93]. Moreover, thiazides can aggravate renal magnesium wasting, often leading to their discontinuation [5, 92, 94]. The serum magnesium level tends to remain low despite high-dose magnesium supplementation [78].…”
Section: Familial Hypomagnesemia With Hypercalciuria and Nephrocalcinmentioning
confidence: 99%
“…5 Zimmermann et al studied the efficacy of hydrochlorothiazide (HCT) in FHHNC patients in a clinical trial, and concluded that HCT is effective in reducing hypercalciuria due to CLDN16 mutation on a shortterm basis; however, the efficacy of HCT to attenuate disease progression remains to be evaluated. 6 No functional studies were performed and we considered the amino acid change in the gene as pathogenic (i.e., mutation) based on the following: (1) positive segregation in the family as parents were heterozygous, (2) the amino acid change is in a region with a predilection to mutation, (3) the changed amino acid is in a conserved residue.…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of these treatments on the course of nephrocalcinosis and on the decline of GFR in FHHNC is unknown. Hydrochlorothiazide has been shown to be effective in correcting hypercalciuria due to CLDN16 mutations in some [52,79] but not all patients [50][51][52]. Mg 2+ supplementation might also be ineffective to correct hypomagnesemia [50][51][52].…”
Section: Prognosis and Treatmentmentioning
confidence: 99%